From Browsing to Buying More: The Journey of Cross-Selling and Upselling in E-Commerce - Olalekan Ezekiel Ajayi (Journal of Consumer Sciences, 2026)
Background: The rapid growth of e-commerce has positioned algorithm-driven recommendation systems, such as cross-selling and upselling, as key tools for enhancing customer engagement and transaction value. However, how consumers in developing countries like Nigeria view and react to these systems has received little empirical attention. Purpose: The study examines how cross-selling and upselling recommendation systems affect consumers' purchasing decisions in Nigeria's rapidly expanding e-commerce sector. Method: The study used a quantitative cross-sectional research design based on survey data obtained from 778 Nigerian customers sampled using the snowball sampling technique, who have previous experience shopping using e-commerce sites. PLS-SEM was used for data analysis. Findings: Perceived usefulness is influenced by perceived ease of use. Purchase intention is positively impacted by perceived usefulness. It has been demonstrated that trust plays a significant role in positively influencing both purchase intention and acceptance of recommendations. Conclusions: This research offers three noteworthy insights. The first contribution relates to TAM's usefulness in algorithm-based recommendation systems, where the theory continues to be useful. Second, the concept of trust is added to the theory and serves as another dimension influencing consumer behavior. Third, the channel from acceptance to higher transaction value is validated empirically. Research Implications: In practical terms, the results imply that e-commerce websites should concentrate on creating user-friendly interfaces, ensuring better recommendations through data personalization, and focus on building trust in customers by ensuring transparency and dependable service delivery.